Comprehensive investigation of coherent optical OFDM-RoF employing 16QAM external modulation for long-haul optical communication system - Anas Ali Hussien; Adnan Hussein Ali (Institute of Advanced Engineering and Science, 2020)
Given the growing need for long haul transmission that requires a high rate of data, the orthogonal frequency division multiplexing scheme (OFDM), is regarded as a technique with high potentials for high-capacity optical networks. OFDM transmits over both optical and wireless channels, with the data distributed over a huge amount of the subcarrier, and the data is distributed over a huge number of subcarriers. OFDM achieves RF signal for a long-haul transmitting by utilizing Radio over Fiber (RoF) system, which is known to produce higher orthogonality of the OFDM modulated signal designed for the wireless network. RoF systems comprise of heterogeneous networks designed through the use of wireless and optical links. The aim of this paper is to carry out an investigation of the performance of the external modulation in RoF links, while analyzing the shortcomings caused by the various elements of the optical system. The Mach–Zehnder modulator (MZM) can be applied in external modulation, and exhibits a more robust performance when implemented with the OFDM modulation technique.